Regional Currency or Regional Trade Policy? An East Asian Perspective of 21st Century Growth - Salim, Ruhul; Kabir, S. (The International Institute of Knowledge Management (TIIKM), 2019)
Being inspired by initial Euro-success, renowned economist Robert Mundell was overoptimistic about adoption of a large currency area in Asia; however, empirical literature on East Asian regional currency is yet inconclusive. Advocates of the optimum currency area (OCA) theory identifies trade enhancement as a major benefit of regional currency adoption. East Asia, however, enjoys high trade enhancement for decades through their ongoing regional integration process in spite of long-practiced controversial individual currency arrangements. As such, a well-managed regional trade policy seems more appropriate for East Asian trade and economic growth. Existing literature consistently ignores the importance of East Asian regional ‘trade policy’ integration and limit the focus to regional ‘trade’ integration motivated by the OCA literature.